Transcatheter interventions in patients with a Fontan circulation: Current practice and future developments - Jalal, Zakaria; Gewillig, Marc; Boudjemline, Younes; Guérin, Patrice; Pilati, Mara; Butera, Gianfranco; Malekzadeh-Milani, Sophie; Avesani, Martina; Thambo, Jean-Benoit (Frontiers in Pediatrics, 2022)
It has been 50 years since Francis Fontan designed the operation that today is offered for a wide range of congenital cardiac lesions with a univentricular physiology. As a result of imaging, surgical, percutaneous and critical care improvements, survival has steadily increased, leading to a currently observed 30-year survival rate up to 80%. However, in the absence of a sub pulmonary ventricle, Fontan circulation is characterized by chronically elevated systemic venous pressures and decreased cardiac output exposing those patients to a large variety of complications. The latter include circulatory failure, Fontan pathway obstructions, ventricular dysfunction, atrioventricular valve regurgitation, arrhythmia, protein-losing enteropathy, or plastic bronchitis. Among the available therapies to treat this specific patient’s populations, various percutaneous cardiac interventions emerged as reliable options, that might either treat a focused lesion or palliate a dysfunction, in order to avoid end-organ failing Fontan status. In this review dedicated to percutaneous therapies in Fontan patients, we will 1) describe the indications, techniques and results of transcatheter approach for basic lesions such as cavo-pulmonary stenosis or collaterals occlusions, 2) highlight the management of a Fontan fenestration during patients course, when percutaneous fenestration closure or creation are needed, 3) detail the basic principles of lymphatic percutaneous interventions in Fontan patients, 4) explore the clinical applications of recent advancement including transcatheter cavo-pulmonary connections or Fontan endovascular valvulation and 5) discuss the future developments of percutaneous therapies in this field.